FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK ORANG TUA DALAM MENGHADAPI PERILAKU SEKSUAL PADA REMAJA TUNAGRAHITA RINGAN DI SLB KOTA SEMARANG - Yekrita Selena Sitohang; Zahroh Shaluhiyah; Laksmono Widagdo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Adolescents with mental retardation have almost the same characteristics as other normal adolescents but experience delays in sensory abilities. The inability of adolescents with mental retardation resist sexual desire causes frustration that disrupts the surrounding environment and triggers the emergence of deviant sexual behavior caused sexually transmitted disease, HIV/AID and unwanted pregnancy. This study aims to analyze the factors associated with the practice of parents in dealing with sexual behavior in mentally retarded adolescents in Semarang City Special School. This research was a quantitative research with cross-sectional approach. The population in this study were parents of mild mental retardation students as many as 45 parents through total sampling The analytical data was conducted univariate and bivariate analysis using Chi Square test. The results showed that there were correlation between age (p = 0,048), knowledge (p = 0,011), attitude (p = 0,014) and teacher support (p = 0,030) with parent practice. There was a need to increase parents' awareness of the dangers of deviant sexual behavior and the importance of openness in teaching sexuality problems to mentally retarded adolescents adjusted to their level of development.